Evidence That CXCL16 Is a Potent Mediator of Angiogenesis and Is Involved in Endothelial Progenitor Cell Chemotaxis: Studies in Mice With K/BxN Serum–Induced Arthritis. Issue 7 (2nd July 2013) - Isozaki, Takeo; Arbab, Ali S.; Haas, Christian S.; Amin, M. Asif; Arendt, Monica D.; Koch, Alisa E.; Ruth, Jeffrey H.
Abstract : Objective: To examine the possibility that CXCL16 recruits endothelial cells (ECs) to developing neovasculature in rheumatoid arthritis (RA) synovium. Methods: We utilized the RA synovial tissue SCID mouse chimera system to examine human microvascular EC (HMVEC) and human endothelial progenitor cell (EPC) recruitment into engrafted human synovium that was injected intragraft with CXCL16‐immunodepleted RA synovial fluid (SF). CXCR6‐deficient and wild‐type (WT) C57BL/6 mice were primed to develop K/BxN serum–induced arthritis and evaluated for angiogenesis. HMVECs and EPCs from human cord blood were also examined for CXCR6 expression, by immunofluorescence and assessment of CXCL16 signaling activity. Results: CXCR6 was prominently expressed on human EPCs and HMVECs, and its expression on HMVECs could be up‐regulated by interleukin‐1β. SCID mice injected with CXCL16‐depleted RA SF exhibited a significant reduction in EPC recruitment. In experiments using the K/BxN serum–induced inflammatory arthritis model, CXCR6 −/− mice showed profound reductions in hemoglobin levels, which correlated with reductions in monocyte and T cell recruitment to arthritic joint tissue compared to that observed in WT mice. Additionally, HMVECs and EPCs responded to CXCL16 stimulation, but exhibited unique signal transduction pathways and homing properties. Conclusion: These results indicate that CXCL16 and its receptor CXCR6 may be a central ligand/receptor pair that is closely associated with EPC recruitment and blood vessel formation in the RA joint.